REDEFINING BOUNDARIES: WOMEN'S STRATEGIC POSITION IN THE EVOLVING INTERNATIONAL PUBLIC REALM - Anadza, Hirshi (Global: Jurnal Politik Internasional, 2024)
The dichotomy of public and private is always related to the binary oppositions of women and men in social realms. Men are always the representation of the public because masculinity emphasises public discourse, war, and peace, and vice versa with women. Consequently, exploring how women position themselves within the international public sphere is imperative, particularly as the boundary between the public and private realms becomes increasingly blurred. This article argues that women could play a crucial role in this more complex public-private dichotomy while facing the international realm. Nation-states have a role as publics domestically but then change their status quo and become private internationally. Besides, the increasing female population in the world also suggests that women's involvement should be considered in any decision-making process. With the help of deductive qualitative analysis and evidence from some parts of the world, this article shows that women should get more involved in the international public realm. At the same time, the public-private dichotomy becomes even more blurred. The increasing level of women's involvement, the blurred public-private dichotomy, and the procrastinating women's involvement are essential evidence of the argument of this article. Instead of debating sexual clichés, this article aims to show that women's involvement nowadays in the international public realm could be a strategic move by a nation-state regarding the domination of private and even public realms.